Implementasi Qris pada UMKM dalam Perspektif Ekonomi Syariah (Studi Kasus di Bank Sampah Hidayah Kota Bengkulu) - Putri Maryani; Fadillah Nurul Fauziah; Uswatun Hasanah (Universitas Muhammadiyah Surabaya, 2026)
The emergence of digital technology in payment systems has encouraged Micro, Small, and Medium Enterprises (UMKM) to switch to cashless payment options, including the introduction of the Quick Response Code Indonesian Standard (QRIS). However, many UMKM, such as Bank Sampah Hidayah located in Bengkulu City, have not yet fully leveraged the benefits of QRIS. This study aims to evaluate the implementation of QRIS in these UMKM through the perspective of Islamic economics. A qualitative approach was used, employing a case study methodology. Data was collected through primary and secondary data namely direct observation and discussions with staff and other parties involved in the daily operations of Bank Sampah Hidayah, as well as the collection of documents from various literature sources, including books, academic journals, and official documents related to QRIS, SMEs, and the principles of Islamic economics. The research findings indicate that QRIS enhances transaction efficiency, simplifies processes, and assists SMEs in maintaining clearer and more efficient financial operations. However, challenges exist, such as limited technological understanding and a societal preference for cash transactions. When evaluated from an Islamic economics perspective, QRIS adheres to the principles of justice and transparency and avoids practices involving riba and gharar, thereby functioning as a legitimate payment method that aligns with the principles of.